Transcranial magnetic stimulation as a promising method of treatment in depression and various neuropsychiatric conditions. A literature review - Kowalczyk, Ilona; Zielonka, Bartłomiej; Stawikowski, Cezary; Krawiec, Paulina; Madej, Karolina; Wolanin, Marta; Wolanin, Izabela; Stachyra, Bartłomiej; Osińska, Aleksandra; Dengler, Barbara (Journal of Education, Health and Sport, 2023)
Background: Transcranial magnetic stimulation (TMS) is a method of non-invasive and painless brain stimulation with an electromagnetic field, which induces changes in the electric field in the brain leading to the cortical activity modulation and stimulation of neurons. Currently, transcranial magnetic stimulation is increasingly used in the diagnosis and treatment of various neuropsychiatric conditions, such as depression, schizophrenia, neurodegenerative diseases, and more. TMS can be used as a method of enhancing the effect of pharmacotherapy as well as a regular treatment. Aim of the study: The study's aim is to summarize the current state of knowledge on transcranial magnetic stimulation as a method of treatment in depression and various neuropsychiatric conditions. Material and methods: The study is based on the literature available in scientific databases such as PubMed, using the following keywords: „transcranial magnetic stimulation”, „tms”, “depression” and “treatment-resistant depression”. Results and conclusions: Transcranial magnetic stimulation is a non-invasive, painless and generally safe method of diagnosis and treatment of many neuropsychiatric diseases, such as depression, schizophrenia, obsessive-compulsive disorders, neurodegenerative diseases, tinnitus, addiction to psychoactive substances and many more. TMS is a well-documented, approved, and recommended treatment primarily for treatment-resistant depression due to its effectiveness, mild side effect profile and good tolerability. Recently there are more and more reports on the effectiveness of TMS in the diagnosis and treatment of other neuropsychiatric conditions, but further research and setting guidelines are needed, so is increasing the availability of the method for patients.